The marshes of southern Iraq: A study in the elements of tourism - Al-Ziyadi, Hussein Alewi Nasser; Ajrash, Hamid Sfyyh (Al-Adab Journal, 2022)
The study is an attempt to define the tourism components in the marshes of southern Iraq and to highlight these components and their role in encouraging and developing tourism in southern Iraq as the most important industries in the modern era and the greatest contribution to the economies of some countries and a new tributary added to the tributaries of the Iraqi economy, and that the goal of the research focuses on the importance of tourism according to the vision Analytical geography, and it included two main axes to achieve this goal, namely, the natural geographical components, the prospects for their investment, and the human and cultural components. the study.